Cuba : os desafios para a construção do socialismo hoje - Stocco, Aline Faé (2013)
In April 2011, during the VI Congress of the Cuban Communist Party, was approved the "Lineamientos de la Politica Economica e Social" the Cuban socialist transition. This fact has consolidated the country a new moment of change in its economic and social model and simultaneously produced mixed reactions among scholar, militants and revolutionaries committed to the Cuban revolution and the building of a society opposed to the logic of capital. Therefore, we sought to analyze the model adopted socialist transition in Cuba with the triumph of the revolution in 1959 until today aiming mainly to identify economic and social aspects for understanding the changes that are currently underway on the island. Using a vast literature on the 53 years of the Cuban socialist transition and document the Cuban Communist Party and the Government of Cuba, it was possible to perform a characterization of the economic and social transition of Cuban socialist, identifying the main changes made to the model as well as the results achieved and produced both in the economic and social point of view. Its main goal is the achievement of a communist society and to the emergence of a new man, was structured in Cuba a model of socialist transition characterized by economic planning, state ownership of the means of production, the elimination of the monetary-market relationships by the combination of moral and material incentives in return to work, by offering a set of basic social services and universal free education and a political-ideological seeking the formation of a socialist consciousness. But over the years the transition model was being changed, and during the 90s, compared to most serious economic crisis facing the country, changes were made that entered the Cuban model of socialist transition elements of the capitalist system as the market private property and foreign capital. Produced a dollarization of the economy that resulted in a dual currency and created targeted markets, both characterized by the use of coins as the rules of marketing. Although he allowed the country regain economic growth and overcome the crisis, these changes have produced negative effects on Cuban society, among which stand out the growing social inequalities, distortions in the labor market and corruption. This new moment of change, and cope with the effects produced by changes of the 90 also seeks to overcome historical challenges of the Cuban economy as high external dependence, low labor productivity, the small food production, among others. The "guidelines" adopted expand the use of market mechanisms within the model of socialist transition in Cuba regarded as the main route for overcoming the major economic problems of the country, expanding the role of private property favoring the creation of a class of owners and eliminate subsidies and gratuities considered egalitarian policies and harmful to the country. Moreover, there was an absence of the politicalideological training for the primary objectives of a socialist transition.